2008
DOI: 10.2353/ajpath.2008.070613
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Nucleoside Depletion Sensitizes to the Mitochondrial Hepatotoxicity of the Reverse Transcriptase Inhibitor Stavudine

Abstract: Stavudine is a hepatotoxic antiretroviral nucleoside analogue that also inhibits the replication of mitochondrial DNA (mtDNA). To elucidate the mechanism and consequences of mtDNA depletion, we treated HepG2 cells with stavudine and either redoxal, an inhibitor of de novo pyrimidine synthesis, or uridine, from which pyrimidine pools are salvaged. Compared with treatment with stavudine alone, co-treatment with redoxal accelerated mtDNA depletion, impaired cell division, and activated caspase 3. These adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
5
27
0
1
Order By: Relevance
“…PGC-1α regulates mt gene transcription via interaction with nuclear respiratory factor 1 (NRF1) and 2, which in turn activates mt transcription factor A (TFAM) [Mallon et al, 2005]. Previous studies found that both PGC-1α and TFAM expressions were elevated in the presence of NRTIs, suggesting a nuclear response to mt toxicity [Mallon et al, 2005;Setzer et al, 2008]. Aside from its role in mt biogenesis, PGC-1α also acts as a modulator of mt AO response by increasing expression of oxidative stress protective genes [Valle et al, 2005;StPierre et al, 2006].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PGC-1α regulates mt gene transcription via interaction with nuclear respiratory factor 1 (NRF1) and 2, which in turn activates mt transcription factor A (TFAM) [Mallon et al, 2005]. Previous studies found that both PGC-1α and TFAM expressions were elevated in the presence of NRTIs, suggesting a nuclear response to mt toxicity [Mallon et al, 2005;Setzer et al, 2008]. Aside from its role in mt biogenesis, PGC-1α also acts as a modulator of mt AO response by increasing expression of oxidative stress protective genes [Valle et al, 2005;StPierre et al, 2006].…”
mentioning
confidence: 99%
“…This opened up investigations into alternate mechanisms of mt toxicity. Other proposed targets of NRTI toxicity include ATP synthesis, mt biogenesis, depleted native nucleotide pools, transcription of mtDNA, mt membrane integrity and transport and protein synthesis [Setzer et al, 2008;Cohen, 2010].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Además se observó aumento en los niveles de transaminasas producto del uso de efavirenz, que alcanzó grado 1 y 2 en nuestros pacientes. Sin embargo, es importante mencionar que existen informaciones sobre hepatotoxicidad grado 3 ó 4 asociada a este medicamento por lo que la monitorización de estos parámetros permitirá su detección precoz y la retirada del medicamento sospechoso de toxicidad 10,32,33 .…”
Section: Discussionunclassified
“…13 Dideoxynucleotide analogs, often used in the treatment of HIV, may impair mitochondrial DNA replication. 13,14 Drug toxicity may also result from the opening of the mitochondrial permeability transition pore (MPTP), which is strongly associated with cell death. 15 ROS generation, ATP depletion, and the aforementioned mitochondrial insults may combine to induce intracellular damage.…”
mentioning
confidence: 99%